Pengaruh Dosis Formula PGPR Asal Perakaran Bambu terhadap Pertumbuhan Tanaman Tomat (Solanum lycopersicum syn) - Iswati, Rida (Jurnal Agroteknotropika, 2012)
This study aims to determine the effect of different doses of PGPR formula from bamboo roots on the growth of tomato. Research using experimental methods in the screen house the Faculty of Agricultural Sciences and its lay out according to randomized complete design with five treatments namely doses 0; 2.5; 5; 7.5, 10 and 12.5 ml of PGPR and each treatment was repeated 4 times. Indicators measured were plant height, leaf number, root number and length. The results showed that plant height and root length increased with increasing dose while the number of leaves and roots showed the highest yield at a dosage of 7.5 ml.